Conversation between Menno Aden and Alejandra Celedón - Aden, Menno; Celedón, Alejandra (Revistarquis, 2014)
ABSTRACT In a conversation with the artist Menno Aden, Alejandra Celedon explores into the artist’s precise, objective and detached views proposing that such records produce a cartography that naturalises the limit between that room and any other. The vast scale of the world is reduced by Aden into a manageable area, that of the room as the building block of strategy of supervision and surveillance. RESUMEN En una conversación con el artista Menno Aden, Alejandra Celedon explora dentro de la meticulosidad del artista, visiones objetivas y desinteresadas proponen que estos registros producen una cartografía capaz de naturalizar el límite entre cuarto (Rooms) y cualquier registro otro. La inmensa escala del mundo reducido por Aden dentro de un área manejable hacen del cuarto l apiedra angular de la supervisión y la vigilancia.